Does knowledge base compatibility help or hurt knowledge sharing between suppliers in coopetition? The role of customer participation - Ho, Hillbun Dixon (2014)
Competing suppliers that collaborate to serve downstream original equipment manufacturer customers often encounter partners with overlapping and compatible knowledge bases. Such knowledge base compatibility provides supplier partners the opportunity to exchange knowledge efficiently, leading to greater knowledge sharing. However, the ease of misappropriation of the shared knowledge can offset this beneficial effect. This research proposes that the effect of knowledge base compatibility on supplier partners' knowledge sharing is moderated by the customer's participation in the collaborative effort and by the customer value such effort creates. The results of two empirical studies show that when levels of both customer participation and customer value are high, knowledge base compatibility between supplier partners leads to greater knowledge sharing. In contrast, when customer participation is high but customer value is low, knowledge base compatibility leads to lower levels of supplier knowledge sharing. This investigation validates the importance of key factors related to supplier partners' opportunity and motivation to share knowledge in coopetitive partnerships.